ANALISIS HASIL EVALUASI REMAJA GENERASI Z DI KARANGASEM TERHADAP NARASI VISUAL ANIMASI 2D “MENGUNGKAP AKAR PERADABAN KARANGASEM” - Wina Pertiwi putri Wardani; I Nyoman Larry Julianto; I Wayan Swandi (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
The use of the internet as a source of information is very familiar to Generation Z, so a learning model that can meet the desires of Generation Z as an audience. Knowing the audience's response from Generation Z to the visual narration of a 2D animated video with an animated sample entitled " Mengungkap Akar Peradaban Karangasem " and the topic of cultural education by the Bali Archaeology Center needs to be investigated. The animated video is a medium of interaction and information from the results of archaeological research with an effort to strengthen the nation's cultural treasures and national character education for the community. The use of animated videos is believed to help to learn, but to what extent animated video visuals can be accepted by the audiences needs to be explored, and methodological action through this research is one of them. This research methodology is qualitative, sourced from observation, interviews, documentation and literature. This study found three audiences' responses: dominant hegemonic position, negotiated, and oppositional. It is dominated by the type of negotiated position caused by the characteristics of generation Z (FOMO, realistic, and phigital). Negotiated positions can have the opportunity to trigger the curiosity of Generation Z to learn more about their culture. The thing to watch out for is the type of oppositional position because it can form new representations that result in narrative bias. The trigger is boredom caused by internal factors (characteristics of generation Z with short attention) and external factors (audio variety and lack of visual weight due to contrast values intended for balance and unity). Keywords: animation, narrative bias, generation Z, visual narrative